Prevalence of bronchitis in children at Latin America's largest open-pit coal mine - Heli A. Arregocés; Roberto Rojano (Clinical Epidemiology and Global Health)
Background/objectives: Air pollution, the presence of substances that harm other living organisms, results from human activity. Open-pit coal mines are notable sources of particulate matter emissions, which spread over considerable distances and affect surrounding communities. This study aimed to evaluate the influence of prolonged exposure to particulate matter with a diameter of ≤10 μm (PM10) emissions from Latin America's largest open-pit coal mine on bronchitis incidence in children aged 0–4 years. Methods: We collected daily PM10 concentration data from 25 stations between January 2011 and December 2019, monitored every three working days. The AirQ + model was used to estimate the human health impacts of long-term exposure to ambient PM10 using the bronchitis prevalence data from the National Institute of Colombia. Results: From 2011 to 2019, the average daily PM10 levels for the zones directly and indirectly impacted by mining were 37.52 and 31.54 μg/m3, respectively. Approximately 500 bronchitis cases were attributed to PM10 pollution. Moreover, an average reduction of 15 μg/m3 in the annual mean PM10 concentration could prevent 56 bronchitis cases annually in children near the mines. Conclusions: From 2011 to 2019, all monitoring stations consistently recorded more than the World Health Organization's annual average reference of 15 μg/m3. Our findings on the long-term effects of PM10 on bronchitis prevalence underscore the health impact of air pollution, emphasizing the importance of stringent air quality standards, particularly in industrial mining zones. This information is vital for developing, monitoring, and assessing air pollution policies while safeguarding public health.